Utilization of Technology in Physics Education: A Literature Review and Implications for the Future Physics Learning - Faresta, Rangga Alif; Nicholas, Teo Zhao Ser Bryan; Chi, Yixuan; Sinambela, Indah Astri Natalia; Mopoliu, Abdul Ziqron (Lensa: Jurnal Kependidikan Fisika, 2024)
The integration of technology in physics education is transforming teaching methods and learning experiences, offering a dynamic approach to understanding complex concepts that traditional methods struggle to convey effectively. This literature review critically examines the current trends in the utilization of technological tools such as simulations, virtual and augmented realities, and interactive software within physics education. Employing the PRISMA framework, the study analyzed a comprehensive dataset from the SCOPUS database, focusing on publications up to May 1, 2024. The results highlight the substantial benefits of technology in enhancing student engagement and understanding of physics, along with identifying the challenges such as inadequate teacher training and unequal access to technology. The review emphasizes the need for professional development programs and equitable technology distribution to maximize the educational benefits. These findings advocate for an evolved educational model that integrates these technological advances to better prepare students for a future dominated by technology, ensuring that physics education remains both current and effective.